Household models: an historical perspective - Patricia Apps; Ray Rees (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper is a survey of the literature on theoretical models of the household, paying particular attention to some of the earlier contributions, and using them to place the current state of the theory in perspective. One of its aims is to suggest that the literature's neglect of Samuelson's proposal, that households can be modelled as if they maximised a form of social welfare function, was a mistake. However, the idea following directly from the Nash bargaining models, that the household's preference ordering over the utility profiles of its members depends on exogenous variables, in particular wage rates and non-wage incomes, is an important one. Combined with Samuelson's proposal, it can be made the basis for a general approach to modelling household decision taking, flexible enough to encompass non-cooperative behaviour and Pareto inefficiencies arising out of the inevitable incompleteness and unenforceability of domestic agreements. We also point out the importance of household production and some of the implications of its neglect in modelling households. Above all, the aim is to provide a deeper understanding of the current theoretical literature on household economics by means of a survey of its history.
Keywords: D10; D13; B21; J22; J16; J13; D60; D01; 330; household behavior; family economics; household welfare; time allocation; labor supply; household production; child care; gender; discrimination; cooperative models; noncooperative models; trade models; microeconomic history; Zeitallokation; Arbeitsangebot; Kinderbetreuung; Haushaltsproduktion; Geschlechterdiskriminierung; Privater Haushalt; Familienökonomik; Haushaltsökonomik; Dogmengeschichte